"Stalking Horses": The American Influence on British Civil Nuclear Identity, 1946-1956. Issue 1 (2nd January 2022) - Theaker, Martin
ABSTRACT: This analysis charts the emergence of a distinct British nuclear culture during the early post-war years and investigates the various forms of influence that the United States exercised on its development. Beginning with a disastrous breakdown of transatlantic nuclear co-operation in 1946, it establishes the true degree of sovereignty enjoyed by Britain's nuclear engineers as they navigated a new relationship with a senior partner that acted simultaneously as a vital knowledge donor and commercial competitor. The analysis next highlights how competition with Washington's vast atomic project only magnified the pre-existing appreciation of thrift engrained in British physicists, in turn causing them to develop an institutional self-image that prized nuclear capabilities more for their technical integrity than their political convenience. In this way, Britain's atomic specialists identified a role for themselves as the spiritual guardians of a technology that was just beginning to embark upon a global journey.